2011
DOI: 10.1038/jcbfm.2011.72
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Transcranial Direct Current Stimulation Modulates Activation-Induced Regional Blood Flow Changes during Voluntary Movement

Abstract: Transcranial direct current stimulation (tDCS) is a noninvasive brain stimulation technique that induces changes in cortical excitability: anodal stimulation increases while cathodal stimulation reduces excitability. Imaging studies performed after unilateral stimulation have shown conflicting results regarding the effects of tDCS on surrogate markers of neuronal activity. The aim of this study was to directly measure these effects on activation-induced changes in regional cerebral blood flow (DrCBF) using pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 43 publications
4
43
0
Order By: Relevance
“…Therefore, the actual relevance of anodal versus cathodal stimulation still remains unclear. It seems unlikely that a lack of behavioral changes indicates no neurophysiological changes elicited by the stimulation because previous studies have demonstrated modulation of motor cortical excitability in an opposite direction between the contralateral and ipsilateral sides with bihemispheric tDCS (Paquette et al, 2011;Zheng et al, 2011;Mordillo-Mateos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the actual relevance of anodal versus cathodal stimulation still remains unclear. It seems unlikely that a lack of behavioral changes indicates no neurophysiological changes elicited by the stimulation because previous studies have demonstrated modulation of motor cortical excitability in an opposite direction between the contralateral and ipsilateral sides with bihemispheric tDCS (Paquette et al, 2011;Zheng et al, 2011;Mordillo-Mateos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the relation between training and motor cortical excitability forms an inverse U-shape, which may explain our observation of both improvement and deterioration of fine motor control in the pianists and nonmusicians after facilitating stimulation. Indeed, improved motor performance seems to be associated with reduced excitability enhancement after an initial phase of enhanced excitability of the respective area (Pascual-Leone et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the limitations of this indirect approach, several studies have focused their attention on other neurophysiologic measurements as surrogate markers of tDCS-induced cortical neuromodulatory effects (Brunoni et al, 2011). In this framework, the use of neuroimaging methods, such as functional magnetic resonance (Baudewig et al, 2001;Jang et al, 2009;Kwon et al, 2008;Polania et al, 2012;Stagg et al, 2009a), positron emission tomography Paquette et al, 2011), laser doppler flowmetry (Wachter et al, 2011) and electroencephalography (EEG) (Ardolino et al, 2005;Polania et al, 2010a), have provided further evidence of changes in neural activity induced by tDCS. Moreover, it is understood that, by modulating cortical excitability, tDCS can induce both short-and long-term changes in a polarity-specific manner Paulus, 2001, Nitsche et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] NBS methods, such as conventional repetitive transcranial magnetic stimulation (rTMS), theta burst TMS, or transcranial direct current stimulation, are capable of modulating cortical excitability within a brain region into inhibitory or excitatory direction using either magnetic or electric fields. These effects are foremost local insofar as they directly affect the cortex at the stimulation site, 4 but if the stimulated region constitutes a node within a larger network (eg, human language networks), activity within the entire network might be affected indirectly. 5,6 The effects of NBS on disturbed language networks are not yet fully understood, and various mechanisms have been postulated to explain the compensation of focal disturbances within the functional networks by excitatory or inhibitory effects on different brain regions.…”
mentioning
confidence: 99%